The predictive value of preoperative neutrophil-to-lymphocyte ratio, monocyte-to-lymphocyte ratio, platelet-to-lymphocyte ratio and systemic immune-inflammation index for organ failure following cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: a retrospective analysis - Borges, Eva; Sousa, Miguel; Marum, Susan; Castro, Mario; Bouw, Maria José (International Surgery Journal, 2025)
Background: Several inflammation-based scores such as neutrophil-to-lymphocyte ratio (NLR) monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) have been identified as new prognosticators in several tumors. Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) is a complex procedure with the potential for high morbidity. Our aim is to analyze if biomarkers can be predictor of organ failure after CRS-HIPEC. Methods: A retrospective analysis of all patients admitted to our intensive care unit (ICU) following CRS-HIPEC. The primary endpoint was the need for organ support. Variables considered statistically significant in the univariable analysis were included in a logistic regression. Results: Among 107 patients admitted to the ICU after CRS-HIPEC, 44.8% had organ failure. Patients with postoperative organ failure had higher preoperative NRL and SII. However, these ratios did not independently predict organ failure. Peritoneal cancer index (PCI) was the only significant predictor of organ failure (OR 1.077, p=0.005). Conclusions: This study highlights the complex interplay between systemic inflammation and organ failure following CRS-HIPEC. Although NLR and SII reflected an inflammatory response in patients who developed organ failure, they did not emerge as independent predictors after adjustment for other variables. In contrast, the PCI effectively stratified risk, underscoring the importance of preoperative assessment of disease burden. These findings emphasize the critical role of ICU admission for postoperative monitoring in this high-risk population, as most patients with organ failure experienced multiple organ dysfunction and higher mortality during ICU stay. Overall, inflammatory biomarkers were not found to be significant predictors of organ failure after CRS-HIPEC.